Genetic variability assessment in bread wheat (Triticum aestivum) grown in Algeria using microsatellites SSR markers - KARIMA KARA; MALIKA RACHED-KANOUNI; SAMAH MNASRI; Hichem Khammar; M’BAREK BEN NACEUR (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Kara K, Rached-Kanouni M, Mnasri S, Khammar H, Ben Naceur MB. 2020. Genetic variability assessment in bread wheat (Triticum aestivum) grown in Algeria using microsatellites SSR markers. Biodiversitas 21: 2638-2644. The assessment of genetic diversity is a key step in evaluating the adaptation of populations to new environmental conditions, and thus in the selection of new cultivars. The present investigation aimed to assess genetic variability of bread wheat (Triticum aestivum L.) genotypes grown in Algeria. The 17 hexaploid genotypes of bread wheat were assessed using 16 molecular microsatellites of SSR (Simple Sequence Repeat). Among the 16 microsatellite markers tested, only 11 markers were the most polymorphic and reproducible. The Polymorphism Information Content (PIC) values per locus varied from 0.14 to 0.70 with an average of 0.48 and 0.49. Genetic similarity between genotypes varied from 0.27 and 0.92 with an average of 0.60. The highest genetic distance value of 0.92 has been scored between Kauz/Pastor/Fiscal and Wbll1*2/Brambling. The lowest value of 0.27 has been scored between Cham6 and Pastor/Wbll1. Genetic similarity was calculated by molecular derived data and used to produce a dendrogram. The genotypes were grouped in two clear clusters according to their origin and pedigree. The first cluster included wheat genotypes Ain Abid (local genotypes), Attila/2 Pastor, and 5119 (introduced genotypes). The second group revealed high polymorphism and was subdivided into four sub-groups. This high level of diversity revealed among the accessions of wheat, grown in Algeria could be used in breeding programs.